2021
DOI: 10.1016/j.ejca.2021.02.030
|View full text |Cite
|
Sign up to set email alerts
|

Novel PD-1 inhibitor prolgolimab: expanding non-resectable/metastatic melanoma therapy choice

Abstract: Background: Prolgolimab is an IgG1 antiePD-1 (programmed cell death protein 1) monoclonal antibody containing the Fc-silencing 'LALA' mutation. We assessed the efficacy and safety of two dosing regimens of prolgolimab in patients with advanced melanoma in a multicenter open-label parallel-arm phase II trial (MIRACULUM). We present the final analysis after 1 year of follow-up and additional efficacy results from 2 years of follow-up. Methods: Patients with advanced cutaneous or non-cutaneous melanoma, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
20

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 26 publications
0
20
0
20
Order By: Relevance
“…In 2021, two additional FDA approvals were granted: tisotumab vedotin for second-line r/mCC and pembrolizumab combined with chemotherapy ± bevacizumab for first-line PD-L1-positive persistent or r/ mCC. With at least 2 dozen additional immunotherapies in clinical trials (Table 1) [31][32][33][34][35][36][37][38][39], the treatment landscape for cervical cancer is on the verge of a paradigm shift. Multiple compounds are in various stages of development that examine the potential for improvement in efficacy and safety in different treatment lines and cervical cancer stages.…”
Section: Introductionmentioning
confidence: 99%
“…In 2021, two additional FDA approvals were granted: tisotumab vedotin for second-line r/mCC and pembrolizumab combined with chemotherapy ± bevacizumab for first-line PD-L1-positive persistent or r/ mCC. With at least 2 dozen additional immunotherapies in clinical trials (Table 1) [31][32][33][34][35][36][37][38][39], the treatment landscape for cervical cancer is on the verge of a paradigm shift. Multiple compounds are in various stages of development that examine the potential for improvement in efficacy and safety in different treatment lines and cervical cancer stages.…”
Section: Introductionmentioning
confidence: 99%
“…The current focus of research lies on newer and hopefully more efficient immune checkpoint inhibitors. Tjulandin et al reported results of the MIRACULUM study, exploring the potential of prolgolimab, an advanced anti-PD-1 ( programmed cell death protein 1) monoclonal antibody at two different dosing schemes [ 76 ]. An objective intracranial response was seen in approximately 50%, and the averaged OS of the patients with brain metastases was 11 months.…”
Section: Resultsmentioning
confidence: 99%
“…Важным этапом эволюции терапевтических моноклональных антител стало появление антител на основе IgG1 с генно-инженерной мутацией LALA (L234A/L235A) в Fc-фрагменте [17]. МКА с мутацией LALA (пролголимаб) связываются с рецептором FcγRI в значительно меньшей степени по сравнению с антителами IgG4 с заменой S228P [18].…”
Section: Conflict Of Interestunclassified
“…Таким образом, антитела к PD-1 с мутацией LALA могут обладать потенциальными преимуществами при проведении анти-PD-1-терапии за счет предотвращения взаимодействия между Fc-фрагментом и FcγR, экспрессируемыми на различных иммунных клетках, в результате чего блокируются возможные эффекторные функции этих антител [17].…”
Section: Conflict Of Interestunclassified